Uncommon Electromagnetic Radiations Related to Extra-High Voltage/Ultra-High Voltage Power Projects in China - Wu, Jing; Zhang, Jingwen; Xie, Li (Frontiers in Environmental Science, 2022)
Based on the high-resolution electromagnetic field intensity observed by the DEMETER satellite, the harmonic electromagnetic radiations in the ionosphere closely above the extra-high voltage (EHV) and ultra-high voltage (UHV) power projects in the Chinese power grid have been detected. In the time-frequency spectrograms, these radiations are characterized by parallel spectral lines with spacings of 50, 100, 150, or 600 Hz. The highest frequency can reach approximately 8850 Hz. The radiations are probably attributed to the nonlinear devices such as converters or geomagnetic disturbance. The harmonic radiations over alternating current-to-direct current (AC-to-DC) substations of power system are generally more diverse and stronger than those over AC-to-AC substations. The measurements on the ground demonstrate that the weak magnetic radiations at several kilohertz with an intensity in the order of nT do exist around substations. A simple physical model is established to understand the characteristics of harmonic radiations propagating from the Earth’s surface to the ionosphere.